Dacryocystography in a cat with orbital pneumatosis. (14th October 2013) - Meomartino, Leonardo; Pasolini, Maria P.; Lamagna, Francesco; Santangelo, Bruna; Mennonna, Giuseppina; Della Valle, Giovanni; Lamagna, Barbara
Abstract A 2‐year‐old neutered male European short‐haired cat was presented for a persistent discharge from the scar of previous left eye enucleation, performed 6 months prior by the referring veterinarian. A surgical exploration of the orbit was performed and retained nictitating membrane glandular and conjunctival tissues were removed. Eleven days later, the cat developed an orbital pneumatosis caused by retrograde movement of air through a patent nasolacrimal system and diagnosed by survey radiographic examination of the skull. Nasolacrimal system patency was assessed by dacryocystography performed by injection of iodinated contrast medium under pressure into the orbital cavity. Computed tomography dacryocystography confirmed the radiographic findings. The condition resolved following dacryocystography, possibly as an inflammatory response to the contrast medium. To our knowledge, this is the first case of orbital pneumatosis reported in a cat.